2021
DOI: 10.3390/plants10081537
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Fortification Alters the Growth, Antioxidant Characteristics and Secondary Metabolite Profiles of Cauliflower (Brassica oleracea var. botrytis) Cultivars in Hydroponic Culture

Abstract: Nowadays the importance of selenium for human health is widely known, but most of the plants are poor in terms of selenium storage and accumulation because of the low selenium mineralization potential of the soil. For this purpose, foliar application of different sodium selenate concentrations (0, 5, 10, 15, 20 mg/L) was used to treat the cauliflower cultivars “Clapton” and “Graffiti”. Higher yields and other related vegetative attributes were improved at 10 and 15 mg/L sodium selenate application. At a concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…The present study further revealed that selenate improved in part (though not consistently) the total antioxidant activity (FRAP) of pea seeds (Table 1, Figures 1C, D). Beneficial effects of foliar-applied selenate on total antioxidant activity were also reported previously for pea seeds (68) and cauliflower florets (70), although different tests were employed (2,2-diphenyl-1picrylhydrazyl; DPPH and/or photochemiluminescence). D'Amato et al (73) emphasized that stress in the plant, induced by increased Se levels, activates the phenylpropanoid pathway involved in the biosynthesis of phenolic compounds (including phenolic acids), which may enhance the scavenging capacity of reactive oxygen species (ROS).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The present study further revealed that selenate improved in part (though not consistently) the total antioxidant activity (FRAP) of pea seeds (Table 1, Figures 1C, D). Beneficial effects of foliar-applied selenate on total antioxidant activity were also reported previously for pea seeds (68) and cauliflower florets (70), although different tests were employed (2,2-diphenyl-1picrylhydrazyl; DPPH and/or photochemiluminescence). D'Amato et al (73) emphasized that stress in the plant, induced by increased Se levels, activates the phenylpropanoid pathway involved in the biosynthesis of phenolic compounds (including phenolic acids), which may enhance the scavenging capacity of reactive oxygen species (ROS).…”
Section: Discussionsupporting
confidence: 73%
“…The present study further revealed that selenate improved in part (though not consistently) the total antioxidant activity (FRAP) of pea seeds ( Table 1 , Figures 1C , D ). Beneficial effects of foliar-applied selenate on total antioxidant activity were also reported previously for pea seeds ( 68 ) and cauliflower florets ( 70 ), although different tests were employed (2,2-diphenyl-1-picrylhydrazyl; DPPH and/or photochemiluminescence).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Optimal doses of Se were known to cope up various types of biotic and abiotic stresses, including exposure to HMs by the regulation of antioxidant system [100]. Selenium is also a fundamental part of some antioxidant enzymes, which shield cells from being damaged by ROS [101,25]. Additionally, reports also showed that an ideal concentration of Se (1/2 µM) enhanced the antioxidant capabilities of photosynthetic pigments and slowed the ageing of leaf tissues in Brassica oleracea [102,25].…”
Section: Glycine Max As 25 μMmentioning
confidence: 99%
“…Among all the classes of SMs, phenolics are one of the major classes of SMs that participate in plant secondary defense. However, the exogenous supply of Se significantly enhanced the levels of phenolic metabolites under different type of metal stresses [25][26][27]13]. Furthermore, antagonistic results of Se on the production glucosinolates (GLS) were also observed in plants when exposed to metalloid toxicity [28][29][30].…”
Section: Introductionmentioning
confidence: 99%